2015
DOI: 10.4236/ojmm.2015.53016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Two Selective Enrichment Media and Two Selective Plating Media for the Detection of <i>Salmonella</i> from Primary Poultry Production, According to ISO 6579:2002

Abstract: Salmonellosis remains a major problematic food born zoonosis worldwide. Poultry and poultry products have been frequently incriminated as the major sources for the aetiological agent, Salmonella species. The implementation of appropriate surveillance and monitoring programme for food safety ultimately requires the examination of food for the presence of food borne pathogens. This study was aimed at evaluating the effectiveness of Modified Semisolid Rappaport-Vassiliadis (MSRV) and Muller-Kauffmann tetrathionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies have also found out that the low specificity of XLD medium created a high number of false positive identification of Salmonella species (Rall et al, 2005;Hyeon et al, 2012;Yhiler et al, 2015). Rall et al (2005) stated that XLD allows the growth of selective bacteria with Salmonella, Proteus, and Citrobacter that displayed similar characteristics as negative lactose fermentation and negative hydrogen sulfide (H 2 S) production on this classical medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also found out that the low specificity of XLD medium created a high number of false positive identification of Salmonella species (Rall et al, 2005;Hyeon et al, 2012;Yhiler et al, 2015). Rall et al (2005) stated that XLD allows the growth of selective bacteria with Salmonella, Proteus, and Citrobacter that displayed similar characteristics as negative lactose fermentation and negative hydrogen sulfide (H 2 S) production on this classical medium.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the colonies of Proteus and Citrobacter probably appear and identified as presumptive Salmonella colony on XLD medium. In addition, Hyeon et al (2012) and Yhiler et al (2015) concluded that XLD medium had high sensitivity but with low specificity for the detection of Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…One colony from each plate that appeared to be Salmonella spp. was chosen for additional examinations based on appearance [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there may have been Salmonella isolates present in the food samples in this study that were missed by all methods. Yangkam Yhiler et al [48] evaluated culturing methods for detecting NTS from chicken, and also found they detected more NTS from chicken by using both MSRV and MKTTn enrichment, but that MSRV was more sensitive. They used XLD and Brilliance Green (BG) for culturing and confirmed NTS using biochemical testing and polyvalent antisera, whilst in this study we used the higher resolution WGS to identify and characterise serovars.…”
Section: Discussionmentioning
confidence: 99%